Health‐Related Quality of Life in Patients with Breast Cancer in Latin America and the Caribbean: A Systematic Review and Meta‐Analysis. (25th February 2021) - Gonzalez, Lucas; Bardach, Ariel; Palacios, Alfredo; Peckaitis, Claudia; Ciapponi, Agustin; Pichón‐Riviere, Andres; Augustovski, Federico
Abstract: Background and Objectives: Breast cancer (BC) is the most common cancer in women. It imposes a huge disease burden and a significant impact on health‐related quality of life (HRQoL). Our study focused on HRQoL of patients with BC in Latin America and the Caribbean (LAC). We conducted a systematic review to identify relevant articles published between 2008 and August 2018. We conducted several meta‐analyses and subgroup analyses by country, disease stage, and instrument used (Prospective Register Of Systematic Reviews registration number: CRD42018106835). Results: From 2, 265 initial references, we finally included 75 articles (8, 806 participants) that assessed HRQoL. The European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire C30 and B23 modules (34 studies; 8 countries; 4, 866 participants) were the most used instruments, followed by the Short Form 36‐item, the abbreviated version of the World Health Organization Quality of Life instrument, and the Functional Assessment of Cancer Therapy – Breast instrument. Only four studies reported specific HRQoL data of patients with metastatic disease. Half the studies were rated as having moderate quality (38/75), and 38% (29/75) as high quality. We identified substantial heterogeneity. As expected, the meta‐analyses revealed that patients with metastatic disease reported lower HRQoL values and high symptom burden compared with patients at earlier stages. Similar results can be observed when we compared patients with early breast cancer in active treatment phases versus those in follow‐up. Conclusion: This study provides a synthesis of breast cancer HRQoL reported in LAC and exposes existing evidence gaps. Patients with BC in active treatment or with metastatic disease had worse HRQoL compared with survivors during the follow‐up period. Implications for Practice: This systematic review provides an exhaustive synthesis of breast cancer health‐related quality of life in women in the Latin American and Caribbean region. Patients with breast cancer in active treatment or with metastatic disease had worse health‐related quality of life compared with survivors during the different follow‐up periods. This study also shows important evidence and methods gaps that can help inform future research. Abstract : This review reports the health‐related quality of life for patients with breast cancer living in Latin American countries and explores relationships with disease stage and treatment in real‐world settings.